Ultra-broadband achromatic metalens with high performance for the entire visible and near-infrared spectrum - Yechuan Zhu; Guangmin Yuan; Ying Chang; Shun Zhou; Chunfang Wu; Yao Li; Weiguo Liu (Results in Physics, 2023)
Metalenses provide unprecedented opportunities to overcome the limitations of conventional refractive lenses, which have been extensively studied to achieve achromatic focusing and imaging in various wavebands. However, it is a challenging task to create a metalens that can achieve achromatic focusing with high efficiency for a broad bandwidth covering the entire visible and near-infrared spectrum. Here, we present a design to overcome the difficulty by employing two types of silicon nitride pillars with different cross sections as optical phase shifters. Numerical results demonstrate diffraction-limited achromatic focusing for the ultra-broad bandwidth from 400 to 1120 nm. All the focal spots at different wavelengths are almost in the same position. The maximum focal shift from the metalens focal length over the ultra-broad waveband is less than 3 %. And the average transmittance and focusing efficiency are 90.2 % and 77.7 %, respectively. These results indicate significant improvement over the previously reported achromatic metalenses in terms of focal-shift suppression and wideband operation with high efficiency. The research provides a means to develop a high-quality achromatic metalens for the entire visible and near-infrared spectrum.